Kesiapan Transisi KUHP Baru Menjelang 2 Januari 2026: Harmonisasi Norma dan Kepastian Hukum Penegakan (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the legal readiness for the transition to Indonesia's new Criminal Code before 2 January 2026 after the enactment of Law Number 1 of 2023 on the Criminal Code and Law Number 20 of 2025 on the Criminal Procedure Code. The issue is legally significant because substantive criminal law and criminal procedure are scheduled to take effect on the same date, while cases that are already in progress, implementing regulations, and the continued temporary use of older procedural instruments still require orderly harmonization. Using normative legal research with statutory and conceptual approaches, this article maps the transitional design of both statutes, identifies the principal points that determine legal certainty in enforcement, and formulates a harmonization model focused on case-stage classification, the application of the more favorable law, and the auditable continuity of compatible implementing rules.
Keywords: Criminal Code; Criminal Procedure; Legal Transition; Legal Certainty; Law Enforcement